Can Ratings Have Indirect Effects? Evidence from the Organizational Response to Peers' Environmental Ratings. (February 2015) - Sharkey, Amanda J.; Bromley, Patricia
Organizations are increasingly subject to rating and ranking by third-party evaluators. Research in this area tends to emphasize the direct effects of ratings systems that occur when ratings give key audiences, such as consumers or investors, more information about a rated firm. Yet, ratings systems may also indirectly influence organizations when the collective presence of more rated peers alters the broader institutional and competitive milieu. Rated firms may be more responsive to ratings systems when surrounded by more rated peers, and ratings may generate diffuse or spillover effects even among unrated firms. We test these arguments by analyzing how rated and unrated firms change their pollution behavior when more firms in their peer group are rated on environmental performance. Results indicate that the presence of more rated peers is often associated with emissions reductions. This relationship varies, however, by whether a firm was rated, whether the rating was positive or negative (if rated), and, often, features of the competitive and regulatory environment.